Estimated dose to site of loco-regional recurrence after radiotherapy in anal cancer using point of origin methods. (January 2023) - Lycke Wind, Karen; Garm Spindler, Karen-Lise; Maria Lutz, Christina; Nyvang, Lars; Kronborg, Camilla
Abstract: Background and purpose: Loco-regional recurrence (LRR) dominates the failure pattern after curative radiotherapy in anal cancer. The aim of this study was to estimate dose of LRRs in anal cancer using a point of origin-based method. Method and materials: Of 321 patients with squamous cell carcinoma of the anus, 31 patients with LRR (29 local recurrences and 5 regional lymph node recurrences) were available for analysis. The recurrence volumes were delineated on recurrence magnetic resonance imaging (rMRI). Rigid and subsequent deformable co-registration of planning computerised tomography scans and rMRI were performed. Point of origin was estimated as the centre of mass (COM) and an observer-based point of origin (obs-PO). Doses to COM and obs-PO, as well as the full recurrence volume, were estimated and the relation to target volumes was extracted. Results: The median minimum dose to COM was 63.8 Gy (range 32.5–65.1 Gy) and 63.7 Gy (range 35.5–65.2 Gy) to obs-PO of local recurrences. COM was included in the high dose volume (64 Gy) in 86 % of cases, and obs-PO was included in 75 % of cases. There was no difference in minimum dose to COM and obs-PO, and the median distance between the two points was 3.3 mm (range 0.6–19.8 mm). No recurrences occurred in primarily boosted lymph nodes. Conclusion: The majority of LLRs were located within the high dose volume indicating radioresistance as the primary cause of recurrence in anal cancer. No difference between the use of COM and obs-PO was evident.